Effects of hydroperiods and predator communities on Pseudacris maculata: a model species for climate change impacts on amphibians - Amburgey, Staci Marie, author; Funk, W. Chris, advisor; Murphy, Melanie, committee member; Muths, Erin, committee member; Bailey, Larissa, committee member; Poff, LeRoy, committee member (Colorado State University. Libraries, 2013)
To view the abstract, please see the full text of the document.
Keywords: hydroperiod; predator cue; phenotypic plasticity; metamorphosis; occupancy; amphibian ecology